Indonesian Pesantren and Community Social Change: Moderate Islam’s Use of Media and Technology for Nonformal, Community-Based Education - Jeffrey A. Ritchey; Nurhaya Muchtar (Adult Education Research Conference, 2014)
This study extends previous research, attempting to better understand pesantren (Indonesian, Islamic boarding schools) by examining factors facilitating the adoption and application of new media and technology in their broader, community-based educational initiatives.